Produksi IgY Spesifik Staphylococcus aureus dari Isolat Asal Kasus Staphylococcosis pada Kelinci - Triwardhani Cahyaningsih; Fachriyan Hasmi Pasaribu; Agustin Indrawati (Institut Pertanian Bogor, 2017)
This experiment aims to produce immunoglobulin Y (Ig-Y) Staphylococcus aureus isolates origin staphylococcosis case in rabbits. Vaccination is done several times using Staphylococcus aureus active in 109 cfu/ml. Injecting the chicken is done four weeks in a row, the first week is done by intravenous injection of S. aureus antigens, the second week of the injection sub cutan S. aureus emulsified with Freund's complete adjuvant, followed by the third and fourth week of the injection of S. aureus antigen emulsified with incomplete Freund's adjuvant. Egg samples were taken after four weeks of the last injection for identification, purification, and determination of specific IgY against S. aureus in egg yolk. IgY specificity qualitatively tests performed by the AGP test (To Gel Precipitation). IgY extraction is done using PEG - Ammonium sulfate, purified IgY concentration calculated by the method of Bradford. The results showed that IgY began to be detected in egg yolk at week six after immunization, with the average levels of IgY is 1.7 mg/ml.